2016
DOI: 10.1039/c5fo01017a
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris fruit body extract ameliorates membranous glomerulonephritis by attenuating oxidative stress and renal inflammation via the NF-κB pathway

Abstract: Membranous glomerulonephritis (MGN) is a common pathogenesis of nephritic syndrome in adult patients. Nuclear factor kappa B (NF-κB) serves as the main transcription factor for the inflammatory response mediated nephropathy. Cordyceps militaris, containing various pharmacological components, has been used as a kind of crude drug and folk tonic food for improving immunity and reducing inflammation. The current study aims to investigate the renoprotective activity of Cordyceps militaris aqueous extract (CM) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…In this study, we showed the involvement of NF-κB in pathogenesis of MGN and the inflammatory reaction in MGN can be reduced by TPL and IMD-0354 treatment through inhibiting NF-κB. Previous study have shown that NF-κB subunit p65 and p50 proteins have critical in vivo functions, and the NF-κB pathway activation associated with the inflammatory response in renal disease [39,40]. In agreement with these reports, we also showed that TPL could inactivate NF-κB (p65 and p50) and blocking IκBα degradation thus inhibit inflammation, suggesting a potential attenuating effect of TPL on MGN via suppressing NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, we showed the involvement of NF-κB in pathogenesis of MGN and the inflammatory reaction in MGN can be reduced by TPL and IMD-0354 treatment through inhibiting NF-κB. Previous study have shown that NF-κB subunit p65 and p50 proteins have critical in vivo functions, and the NF-κB pathway activation associated with the inflammatory response in renal disease [39,40]. In agreement with these reports, we also showed that TPL could inactivate NF-κB (p65 and p50) and blocking IκBα degradation thus inhibit inflammation, suggesting a potential attenuating effect of TPL on MGN via suppressing NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…The LC-10ATvp high performance liquid chromatography (HPLC) system (Shimadzu, Japan), equipped with a TSK-GEL G4000PWXL column (Tosho Co., Japan) and a Alltech 2000ES Evaporative Light Scattering Detector (ELSD) (Shimadzu, Japan) were used to evaluate the molecular weights of IO1-IO5 [13]. Double distilled (D.D.)…”
Section: Methodsmentioning
confidence: 99%
“…L. barbarum (obtained from Ningxia province, China) was extracted with water (100 g L. barbarum in 500 ml) twice at 80˚C for 3 h. The collected supernatant was concentrated at 37˚C and 4,000 x g for 10 min and proteins were removed using 50 ml Sevag reagent (n-butanol: chloroform, 1:4 vol). The polysaccharides were purified according to previous methods (16). Following precipitation with 4-fold ethanol at 4˚C for 12 h, the precipitate was dissolved in double distilled water and subjected to a diethylaminoethyl (DEAE)-52 cellulose anion exchange column (2.6 cm x 35 cm; Whatman; GE Healthcare Life Sciences, Little Chalfont, UK) and a gel permeation chromatography system (Sepharose G-100; Pharmacia; GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%